Sternocostal Dislocation Following Open Correction of Pectus Excavatum–“Stairway Phenomenon”: Complication Management by Means of Sternocostal Locking Titanium Plate Osteosynthesis - Schulz-Drost, Stefan; Syed, Julia; Besendoerfer, Manuel; Carbon, Roman T. (The Thoracic and Cardiovascular Surgeon, 2014)
Introduction Some open surgical methods describe complete sternocostal dissection with subsequent resynthesis. Lack of consolidation with painful sternocostal instability and retrosternal dislocation of sternal rib tips are possible complications.Materials and Methods Seven patients with symptomatic unilateral sternocostal dislocation were included in this study. After diagnosis, confirmed by three-dimensional computed tomography (CT), patients underwent open surgery. All affected ribs were reset and fixed to the sternum with the aid of titanium implants.Results The patients had, on average, unilateral dislocation of 3.4 rib joints with 15.4 mm retrosternal dislocation, which was fixed with 2.3 plates. A titanium splint was also employed. The recurrent nature of the problem made procedures very time-consuming (average operation time: 3 hours 25 minutes). One patient suffered strong intraoperative bleeding requiring transfusion of blood products and access enlargement. Follow-up examinations showed high patient satisfaction (grade of 1.7; rating scale 1–6). Remaining rib instabilities were observed just as infrequently as were material failures. The sternocostal rib splint in the costal cartilage became loose and was removed. One patient exhibited a pectoral muscle asymmetry. No other complications were observed.Conclusion The term “stairway phenomenon” describes the dislocation of sternocostal joints. Observed after open pectus excavatum correction it can trigger substantial physical complaints. Thus, preserving those joints during pectus repair is strongly recommended. Locking titanium plates are a safe alternative to sternocostal suture fixation and is characterized by high patient satisfaction.
Keywords: chest wall; pectus excavatum; pectus carinatum; locking plate; complications; reoperation; outcomes; surgical equipment